Kehidupan Sosial Masyarakat Arab Masa Awal Kehadiran Pendidikan Islam - Satir, Muhammad (Tarbiyah STAIN Sorong, 2019)
The social condition of the Arabs before Islam was known as the 'period of ignorance' or the age of ignorance, caused by social, political, morality and social relations in real conditions of error. To understand the jahiliyyah habits of the Arabs, the all-wise God sent an Apostle, Muhammad SAW. polite, humble, generous, brave, honest and trustworthy, they believe in